Effects of drought stress on water content and biomass distribution in summer maize(Zea mays L.) - Yan, Siying; Weng, Baisha; Jing, Lanshu; Bi, Wuxia (Frontiers in Plant Science, 2023)
The resource allocation of different component organs of crops under drought stress is a strategy for the coordinated growth of crops, which also reflects the adaptability of crops to drought condition. In this study, maize variety namely 'Denghai 618' ,under the ventilation shed, two treatment groups of light drought (LD) and moderate drought (MD) and the same rehydration after drought are set, as well as the normal water supply for control in shed (CS), the drought experiment was conducted in the jointing-tasseling stage in 2021. The effects of different drought stress on water content and biomass allocation of each component organ were analyzed. The results showed that: (1) During the drought period, the water content of each component organ of summer maize decreased in general, but the WCDR of root increased 1.83% ~ 2.35%，the WCDR of stem increased 0.52% ~ 1.40%. (2) Under different drought treatments, the root biomass (RB) increased 33.94% ~ 46.09%，and fruit biomass (FB) increased 1.46% ~ 2.49%， the leaf biomass (LB) decreased by 8.2% and 1.46% respectively under LD and MD. (3) The allometric growth model constructed under sufficient water is not suitable for drought stress, the allometric exponent α under drought stress lower than that of the CS: CS (α=1.175)＞MD (α=1.136)＞LD (α=1.048), which also indicates that the impact of existing climate change on grain yield may be underestimated. This study is helpful to understand the adaptive strategies of coordinated growth of maize component organs under drought stress, and provide a reference for the prediction of grain yield under climate change.